A Spatial Analysis For The Phenomenon Of Financial And Administrative Corruption In Iraq And Its Political And Economic Effects - Kelaiwy, Lateef Kamel (International Journal of Psychosocial Rehabilitation, 2020)
The phenomenon of financial and administrative corruption is one of the most prominent challenges that faced the Iraqi state after 2003 due to its profound effects on the building of the state and its economic structure. Corruption is a political, economic, administrative, and social phenomenon that is basically extracted from the exploitation of power or influence in order to achieve material or moral gains by illegal means. There is no more evidence for this than listing Iraq as the world’s most corrupt country. This phenomenon has grown and increased until its features are engraved and rooted in the state and this has been confirmed by the reports of Transparency International since 2004. These reports showed that Iraq occupies an advanced position among the most financially and administratively corrupt countries. This is due to the weakness of the official agencies concerned with confronting corruption on the one hand, and the control of utilitarian parties aspiring to maximize their gains at the expense of the people through corruption on the other. The phenomenon of financial and administrative corruption in Iraq has hampered the process of building and progress in the state at the political and economic levels. Accordingly, this research came to delve into the nature of this phenomenon and its causes and to propose solutions to confront it.